2015
DOI: 10.1093/jamia/ocv074
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of a primary care electronic medical record system in three Kenyan rural health centers

Abstract: We successfully implemented a primary care EMR in three rural Kenyan health centers. Patient waiting time was dramatically lengthened while the nurses' and the clerks' patient care time decreased. Long-term use of EMRs in such settings will require changes in culture and workflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…A possible reason is the recent introduction of the EMR system at those centers, as most studies indicated that waiting time tends to improve with time. A mixed methodology study exploring patients' perception of EMR implementation indicated an 85% positive perception, which was mainly in the clinical care theme [22].…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason is the recent introduction of the EMR system at those centers, as most studies indicated that waiting time tends to improve with time. A mixed methodology study exploring patients' perception of EMR implementation indicated an 85% positive perception, which was mainly in the clinical care theme [22].…”
Section: Discussionmentioning
confidence: 99%
“…4 Nuffield Department of Primary Care Health Sciences, University of Oxford, Oxford, UK. 5 Brown Center for Biomedical Informatics, Brown University, Providence, RI, USA.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Over the last two decades, digital health systems for hospitals and clinics have been rapidly adopted in high-income countries [1][2][3]. This move away from paper-based storage and retrieval of medical information to digital systems opens the opportunity for new ways of delivering care and a better understanding of the processes and outcomes of the health service [4][5][6]. Along the way, these countries have invested large sums and had multiple challenges and failures [3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…National-level implementations of EHRs in many LMICs primarily aim to support HIV care and treatment, with funding for these systems coming from programs such as the US President's Emergency Plan for AIDS Relief (PEPFAR) (5,6). Several countries, such as Rwanda, Uganda, Mozambique, and Kenya, have gone beyond isolated and pilot implementations of EHRs to large-scale national rollout of systems within government-run public facilities (7). With such large-scale EHRs implementations, these countries are nding themselves in the unenviable position of being unable to easily track the status of each implementation, especially given that most of the EHRs implementations are standalone and are distributed over large geographical areas.…”
Section: Introductionmentioning
confidence: 99%